The semantic Grammatical Study About How in The Holy Quran - Asia Younus Abd (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The Arabic language has served, and continues to serve, as the vessel that preserves these meanings and Quranic connotations. Among the linguistic tools with diverse implications is the interrogative particle "كيف" (how), which carries meanings that go beyond mere inquiry to include nuances such as denial, threat, rebuke, questioning of the manner, and others. This study examines the word "كيف" (How) in the Holy Qur'an from a semantic and grammatical perspective, exploring its various meanings and syntactic roles within different contexts. The study highlights how "كيف" extends beyond its primary function as an interrogative particle to convey rhetorical and semantic nuances such as denial, astonishment, threat, rebuke, improbability, and magnification. By analyzing Quranic verses where "كيف" appears, this research demonstrates the linguistic depth and eloquence of the Qur'an, revealing the role of context in determining meaning. The study employs an inductive and descriptive-analytical approach, compiling occurrences of "كيف" and categorizing them based on their function and rhetorical significance. The findings emphasize the diversity of meanings, illustrating how a single word can contribute to the richness of Quranic expression. Furthermore, this research underscores the necessity of contextual interpretation to fully grasp the nuances embedded within Quranic discourse.